2019
DOI: 10.3201/eid2510.190130
|View full text |Cite
|
Sign up to set email alerts
|

Transmissibility of MERS-CoV Infection in Closed Setting, Riyadh, Saudi Arabia, 2015

Abstract: To investigate a cluster of Middle East respiratory syndrome (MERS) cases in a women-only dormitory in Riyadh, Saudi Arabia, in October 2015, we collected epidemiologic information, nasopharyngeal/oropharyngeal swab samples, and blood samples from 828 residents during November 2015 and December 2015–January 2016. We found confirmed infection for 19 (8 by reverse transcription PCR and 11 by serologic testing). Infection attack rates varied (2.7%–32.3%) by dormitory building. No deaths occurred. Independent risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…Firstly, the cases reported from the North Al Batinah cluster were household contacts, indicating that for the first time in the country human-to-human transmission occurred at the household level. Similar family clusters were reported in Saudi Arabia [14,15,17,[34][35][36][37][38][39], Tunisia [40] and the UK [39]. Secondly, the epidemiological characteristics of these 13 cases are different from what has been observed in cases reported from other countries [5,10,11,39,40].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Firstly, the cases reported from the North Al Batinah cluster were household contacts, indicating that for the first time in the country human-to-human transmission occurred at the household level. Similar family clusters were reported in Saudi Arabia [14,15,17,[34][35][36][37][38][39], Tunisia [40] and the UK [39]. Secondly, the epidemiological characteristics of these 13 cases are different from what has been observed in cases reported from other countries [5,10,11,39,40].…”
Section: Discussionsupporting
confidence: 67%
“…A similar situation was observed in Saudi Arabia, where up to 50% of MERS-CoV cases were classified as secondary, due to possible human-to-human transmission through contact with asymptomatic or symptomatic individuals infected with MERS-CoV [42]. Furthermore, limited human-to-human transmission of MERS-CoV was observed in several other clusters in other countries, including family members [14][15][16][17][18][19] and patients in health care facilities [39,40,[42][43][44].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A comparison of a cohort of [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] year-olds and a cohort of ≥65 year-olds found no clear difference in incidence between the two age groups, as measured by seroconversion or PCRconfirmed, HCoV-associated respiratory illness 120 . Finally, observational studies have shown evidence of coronavirus-associated respiratory illnesses in elderly populations [121][122][123] and across all ages 124 .…”
Section: Seroincidence Of Endemic Coronaviruses Occurs In All Age Gromentioning
confidence: 99%
“…For example, at week 26, there were 12 patients with mild symptoms from studies that reported a cutoff, and 8 of those patients had IgG levels above that cutoff. MERS-CoV data were digitised from six studies 35,40,46,47,142,143…”
Section: Supplementary Data S2: Data Digitized On Cross-reactivity Anmentioning
confidence: 99%